Peningkatan Pendapatan Rumah Tangga Melalui Pemberdayaan Ibu-Ibu PKK - Mia Ajeng Alifiana (Universitas Islam Nahdlatul Ulama Jepara, 2018)
The aim of this dedication is to train the PKK member to make accessories and increase their family income. The partner of this dedication is RT 01 RW 07 in Mlati Norowoti Village, Kudus Regency, especially the PKK group. The methods using in this service are entrepreneurship counseling and training in making hijab handmade accessories. PKK Group was delighthened with this program. They can practice making the accessories from acrylic based. The result of this dedication to the people activity was the PKK group Rt 01 Rw 07, the village of Mlati Norowito has been able to practice and make hijab handmade accessories until it reaches the marketing stage. The accessories have been sold among the member and also the resident of RT 01 RW 07 Mlati Nororwito and it become additional income for the family.